Internet Use for Obtaining Medicine Information: Cross-sectional Survey - Bergmo, Trine Strand; Sandsdalen, Vilde; Manskow, Unn Sollid; Småbrekke, Lars; Waaseth, Marit (JMIR Formative Research, 2023)
Background: The internet is increasingly being used as a source of medicine-related information. People want information to facilitate decision-making and self-management, and they tend to prefer the internet for ease of access. However, it is widely acknowledged that the quality of web-based information varies. Poor interpretation of medicine information can lead to anxiety and poor adherence to drug therapy. It is therefore important to understand how people search, select, and trust medicine information. Objective: The objectives of this study were to establish the extent of internet use for seeking medicine information among Norwegian pharmacy customers, analyze factors associated with internet use, and investigate the level of trust in different sources and websites. Methods: This is a cross-sectional study with a convenience sample of pharmacy customers recruited from all but one community pharmacy in Tromsø, a medium size municipality in Norway (77,000 inhabitants). Persons (aged ≥16 years) able to complete a questionnaire in Norwegian were asked to participate in the study. The recruitment took place in September and October 2020. Due to COVID-19 restrictions, social media was also used to recruit medicine users. Results: A total of 303 respondents reported which sources they used to obtain information about their medicines (both prescription and over the counter) and to what extent they trusted these sources. A total of 125 (41.3%) respondents used the internet for medicine information, and the only factor associated with internet use was age. The odds of using the internet declined by 5% per year of age (odds ratio 0.95, 95% CI 0.94-0.97; P=.048). We found no association between internet use and gender, level of education, or regular medicine use. The main purpose reported for using the internet was to obtain information about side effects. Other main sources of medicine information were physicians (n=191, 63%), pharmacy personnel (n=142, 47%), and medication package leaflets (n=124, 42%), while 36 ...